Pandangan Masyarakat Etnis Batak Toba terhadap Poligami Akibat Tidak Memiliki Anak Laki-Laki - Anggun Luthvita Siregar; Dinda Nur Maulida; Gresia Krisanta Manalu; Rosliana Marbun; Sonia Manihuruk; Lasenna Siallagan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the views of the Toba Batak ethnic community towards polygamy as a result of not having sons, regarding the importance of the role of sons in Toba Batak families, factors causing polygamy, impacts and solutions to prevent polygamy. The method used in this research is a qualitative research method, and data collection techniques in this research use literature study techniques and interviews with Toba Batak ethnic traditional leaders. The research results show that boys have a very important role in the family, namely as successors to the clan, complementing traditional parties, and distributing inheritance. Polygamy can occur due to 2 factors, namely family encouragement and lack of religious learning. The impact of polygamy is that women are excluded and excluded from the community. The solution to preventing polygamy is to explore and build a deep understanding of religious teachings regarding the concept of fidelity in marriage and involving religious figures as the main pillar to build strong understanding and awareness.